2013
DOI: 10.1053/j.gastro.2012.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Pro-Angiogenic Activity of TLRs and NLRs: A Novel Link Between Gut Microbiota and Intestinal Angiogenesis

Abstract: Background & Aims In intestinal inflammation the gut microbiota induces an innate immune response by activating epithelial and immune cells that initiate or maintain inflammation. We investigated whether the microbiota can also activate local microvascular cells and induce angiogenesis. Methods Human intestinal microvascular endothelial cells (HIMEC) and intestinal fibroblasts (HIF) were exposed to bacterial ligands specific for TLR2/6 and 4, and NOD1 and NOD2, and cell proliferation, migration, transmigrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 109 publications
(69 citation statements)
references
References 51 publications
0
69
0
Order By: Relevance
“…The endothelium has been likened to an inner epithelium, serving as a second line of physical boundary against external pathogens (57)(58)(59). Aberrant endothelium in asthma has been recognized for more than a century (3).…”
Section: Discussionmentioning
confidence: 99%
“…The endothelium has been likened to an inner epithelium, serving as a second line of physical boundary against external pathogens (57)(58)(59). Aberrant endothelium in asthma has been recognized for more than a century (3).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, adult germ-free mice were found to have arrested intestinal villi capillary network formation, which was restored 10 days after colonization with a complete microbiota (40). Furthermore, microbial products have been shown to directly activate mucosal endothelial cells and to increase endothelial cell tube formation in vitro (37). However, we found that when neonatal mice were inoculated with adult commensal bacteria together with administration of other stresses including hypoxia, cold stress, and formula feeding, endothelial cell proliferation in the intestinal villi was decreased and intestinal mucosal microvasculature development was impaired.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal angiogenesis is ongoing at the time of acquisition of the microbiome, and a perturbation of angiogenesis may be implicated in intestinal inflammatory conditions such as NEC. In a laboratory model, fibroblasts have been shown to produce proangiogenic factors in response to microbial cell products, and endothelial cells have demonstrated proliferation, migration, tube formation, and vessel sprouting (48).…”
Section: Role Of the Microbiome On Git Development And Maintenance Ofmentioning
confidence: 99%